LAW OF CONSERVATION OF NUMBER TO MEASURE STUDENTS' READINESS TO LEARN MATHEMATICS IN GRADE I ELEMENTARY SCHOOL - Neng Dewi Yuliana; Karlimah Karlimah; Elan Elan (Universitas Majalengka, 2025)
This study aims to measure the readiness to learn mathematics of grade I elementary school students through understanding the law of conservation of number. This law is an important indicator in assessing children's cognitive abilities in understanding that the number of objects remains the same despite changes in arrangement or visual form. The research approach used was qualitative with an exploratory descriptive design. Data were collected through concrete task-based assessments and interviews with class teachers of 25 grade I students in one of the public elementary schools in Tasikmalaya City. The results showed that 48% of students fully understood the concept of conservation of number, 32% showed partial understanding, and 20% did not show adequate mastery of the concept. The analysis showed that visual changes still influenced the perception of quantity in some students, indicating the dominance of preoperational thinking. The conclusion of this study shows that the law of conservation of numbers can be used as an initial assessment tool to accurately map students' readiness to learn mathematics. The results of this assessment can be the basis for designing learning strategies that are contextual, concrete, and in accordance with the stage of cognitive development of children.